Hydrological properties of cork container media - Carmona, E.; Ordovas, J.; Moreno, M. T.; Aviles, M.; Aguado, M. T.; Ortega, M. C. (HORTSCIENCE, 2003)
Static hydrological properties \{[\}aeration capacity; easily available water, reserve water, water release curves: theta(v)(Psi(m)), and specific humidity curves] and dynamic hydrological properties (saturated and unsaturated hydraulic conductivity) of substrates based on industrial cork residue (the bark of Quercus suber L.) and cork compost were studied. Samples of similar granulometry have been used to establish the effect of cork composting on the aforementioned physical properties. Different models were tested to describe the mechanism of water release from these materials. Van Genuchten's model (Van Genuchten, 1978) was the best fit and produced specific humidity curves that revealed slight differences in the ratio of water capacity function. When cork residues were composted for 7 months, important changes occurred in hydrological properties of the material as it became more wettable. Water retention significantly increased from 45% to 54%, at a potential of 5 kPa, although this did not necessarily result in increased water available to plants. A study of the unsaturated hydraulic conductivity (K-unsat) of these materials revealed a significant decrease in the K-unsat water potential at 0-5 kPa, which corresponds to the range in which the irrigation with these substrates was usually carried out. The long composting process resulted in increased K-unsat between 4 and 5 times that of uncomposted material, which would improve the water supply to the plant.
The following values have no corresponding Zotero field: pub-location: 113 S WEST ST, STE 200, ALEXANDRIA, VA 22314-2851 USA publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: growing media; horticultural substrate; hydraulic conductivity; physical properties; water release curves

Nitrogen availability in composted cork - Carmona, E.; Ordovas, J.; Ortega, M. C.; Aguado, M. T. (INTERNATIONAL SYMPOSIUM ON GROWING MEDIA AND PLANT NUTRITION IN HORTICULTURE, 1997)
Previous studies showed that plants grown in fresh cork (Quercus suberL. bark) had a reduced growth compared with peat and low rates of N. In composted cork, however, plant growth was similar with those in peat, but the N content of plants was still slightly lower. The purpose of this study was to investigate N availability in fresh and composted cork during 4, 5.5 and 7 months, using peat as control medium. The substrates were also incubated at 25 degrees C during 60 days after adding 0.25, 1.0, 1.75 or 3.0 g ammonium nitrate per 1 of substrate. Samples were taken periodically to measure NO3-N, NH4-N and total N. Also the Nitrogen Drawdown Index (NDI) for the addition of 75 mg.l(-1) N and 150 mg.l(-1) N was measured after incubation at 25 degrees C. N immobilization rates were well correlated to NDI. NH and soluble N drawed down rapidly in cork substrates while total N stayed constant. High rates of ammonium nitrate should be added to maintain a constant level of available N to plants in cork.
The following values have no corresponding Zotero field: periodical: INTERNATIONAL SYMPOSIUM ON GROWING MEDIA AND PLANT NUTRITION IN HORTICULTURE issue: 450 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: bark; growing media; N immobilization

Characteristics of internal porosity of cork container media - Ordovas, J.; Carmona, E.; Moreno, M. T.; Ortega, M. C. (HORTSCIENCE, 1996)
The structure of cork (Quercus suber L.) bark presents a series of characteristics, suggesting that internal porosity is partly occluded. This study determined the porosity in the waste cork industry (C) and when such waste product had been composted during 4 (CC-4), 7 (CC-7), and 10.5 months (CC-10.5). The particle density of the intact and finely ground material differed significantly in all particle size ranges larger than 0.5 mm. The porosity of the cork substrates ranged from 80% to 94% of the total volume, according to granulometry and the degree of decomposition. However, large particles and less decomposed material with a high porosity had up to 10% of the total volume as occluded pores. The material's effective porosity varied slightly between the various particle sizes and degrees of decomposition, which ranged between 80% and 89%, having an average value of 85%. The ash content was highly correlated with the particle density of the finely ground material. Nevertheless, and due to occluded porosity, we cannot estimate the `'effective porosity'' from the ashes; therefore, we must resort to techniques that involve the displacement of a fluid, such as liquids or gas pycnometry or submersion.
The following values have no corresponding Zotero field: pub-location: 701 NORTH SAINT ASAPH STREET, ALEXANDRIA, VA 22314-1998 publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: ash content; effective porosity; particle density; total porosity